Waste cooking oil biodiesel via a sodium hydroxide-catalyzed transesterification process: effects on diesel engine performance and emissions - Hamid, Abdul; Syafa, Muhammad Badrus; Fatah, Misbakhul; Jakfar, Amin; Rahmawati, Zeni; Purbaningtias, Tri Esti; Fikri, Mohammad Anas; Rohmah, Faizatur; Wilujeng, Auliana Diah (Jurnal Polimesin, 2025)
This study reports the synthesis of biodiesel from locally sourced Waste Cooking Oil (WCO) using sodium hydroxide (NaOH) catalyst. The main objective of this research is to assess the feasibility of utilizing WCO-based biodiesel as a sustainable alternative fuel by analyzing its physicochemical properties and application in a Yanmar® TF 70 LY-DI diesel engine. The production process involved degumming, acid-catalyzed esterification, and base-catalyzed transesterification to address the high free fatty acid content of WCO. The resulting biodiesel met ASTM D6751 standards, with a kinematic viscosity of 5.06 cSt, a flash point of 164°C, a density of 885 kg/m3, a FAME yield of 98.17%, and an acid number of 0.12 mg-KOH/g. Engine tests were performed using blends from B10 to B40 and benchmarked against pure diesel. Results showed that B10 and B20 blends maintained comparable engine performance, while higher blends (B30–B40) exhibited reductions in power and torque and increased Specific Fuel Consumption (SFC). CO emissions decreased significantly with increasing biodiesel content, whereas NO and NOx emissions rose due to higher combustion temperatures. These findings demonstrate the technical feasibility and environmental benefits of WCO-derived biodiesel, particularly at lower blend ratios (≤ B20), as a locally available and sustainable fuel. The study is limited to laboratory-scale testing on a single-cylinder engine without long-term durability assessments, which should be addressed in future studies.